Analysis of the Influence of Instagram, Facebook and Google Maps Marketing on Consumer Buying Interest (Study on Liquid Caffe Kedungpring) - Ahmad Sholichin; Muhamad Imam Syairozi; Abid Muhtarom (Sean Institute, 2025)
Liquid Caffe is one of the businesses in the food and beverage sector, which focuses on attracting consumers to buy products sold at Liquid Caffe Kedungpring. Therefore, this study was conducted to find out the marketing of Instagram, Facebook and Google Maps which affect consumer buying interest at Liquid Caffe Kedungpring. This study aims to determine the influence of Instagram, Facebook and Google Maps marketing on consumer buying interest both partially and simultaneously and the most dominant factor among the three variables that affect consumer buying interest. The population of this study is Liquid Caffe Kedungpring consumers, with a sample of 143 respondents. This study uses quantitative methods, including multiple linear regression analysis methods with the assistance of the SPSS program. From the results of the t-test of the Instagram marketing variable (X1), a significance value of 0.464 > 0.05 was obtained, the Facebook marketing variable (X2) obtained a significance value of 0.187 > 0.05 and the Google Maps marketing variable (X3) obtained a significance value of 0.126 > 0.05. Meanwhile, the R Square value is 0.35 which means that all variables (X1, X2 and X3) simultaneously affect buying interest (Y) by 35%. The results of the study show that Instagram, Facebook and Google Maps marketing do not have a partial effect on consumers' buying interest in Liquid Caffe, because most of the consumers who have buying interest in Liquid Caffe come from word of mouth. The marketing carried out through social media is only as a support, not the main marketing for now.